Age, body posture, daily working load, past antihypertensive drugs and risk of hypertension: A rural Indonesian study (Medical Journal of Indonesia, 2001)
Indonesia has about 210 million inhabitans and most of them live in rural areas, therefore in rural community it is estimated that a big number of hypertensive people can be found. However, few rural community-based studies have been conducted to identify hypertensive risk factors. This study aims to identfy some risk factors related to hypertension in rural areas. The data for this study came from the result of the field study done by the second year medical students of the Faculty of Medicine, University of Indonesia, Jakarta. The study was conducted on July 12, 2000 at 10:00 AM to 1:00 PM in a rural area, the Cijeruk subdistrict in Bogor regency. The subjects were selected randomly using neighborhood cluster. Interviews and blood pressure were taken at the houses of the subjects. The results of this study showed that people aged 40 years or over had an increase risk to suffer hypertension compared to the 17-39 year old group, and the risk was most prominent among the 55-59 year group (adjusted odds ratio = 21.62; 95% confidence intervals (CI) = 4.10-113.97). Compared to the subjects with normal body posture, those who were obese had more than 6.3-folds increase in the risk to be hypertensive (adjusted OR = 6.33: 95% CI = 2.62-15.29). In addition, those who discontinued antihypertensive drugs had almost 12-fold increase in the risk to be hypertensive relative to subjects who never take antihypertensive drugs (adjusted OR = 11.92; 95% CI = 4.61 -30.80). This study concluded that special attention should be taken to the elderly aged 40 years and over, to some one who discontinued antihypertensive drugs, and whom had light daily working load to prevent hypertension. (Med J Indones 2001; 10:29-33) Keywords: hypertensive, risk factor, adjusted odds ratio, elderly.